Honderdvijftig jaar levenslopen : de historische Steekproef Nederlandse bevolking - Maas, I. (Ineke), 1964-; Leeuwen, Marco H. D. van, 1958-; Mandemakers, Kees (Mens en maatschappij. Boekaflevering ;, 2008)
Annotation In the past hundred and fifty years the lives of Dutch men and women seem to have become more varied than ever. However, this doesn't mean that before this time their lives were uniform and unchanging. In this book leading scholars describe the lives and times of Dutch men and women born since 1850 and demonstrate/explain their individual differences. This title can be previewed in Google Books - http://books.google.com/books?vid=ISBN9789089640673. This title is available in the OAPEN Library - http://www.oapen.org.